Reformasi Birokrasi sebagai Strategi Tanggung Jawab Pemerintah pada Pelayan Publik - Agustin Widjiastuti (Jurnal Hukum Lex Generalis, 2025)
The existence of bureaucratic reform that is the responsibility of the government in running the government is very dependent on the good and bad and effective wheels of government bureaucracy as a strategy of government responsibility in public services. The demands of the people's conscience require a government bureaucracy that is able to carry out its duties and functions in serving and empowering the community seriously and responsibly and it is hoped that bureaucrats / officials are able to be role models and role models for the community in running their lives (both in work and personal life) every day. The process of bureaucratic reform desired by the community is the implementation of good governance and this bureaucratic reform will continue until now and until there is no more abuse of power and mismanagement when providing public services and managing state assets for the welfare of the community. The research method used is normative juridical, namely an effort to find a solution to the problem by researching and reviewing positive legal norms by conducting literature studies. The results of the study indicate that the bureaucratic reform policy has provided rules that guarantee that public interests, increased welfare and social justice for all people can be reflected / implemented through bureaucratic reform policies that are implemented in accordance with the principles of good governance as stated in the general principles of good governance. However, there still needs to be improvement in implementing the principles of bureaucratic reform optimally and conducting surveys related to government actions and public compliance.